Imagine arts: now the arts can transform care homes - Broome, Emma; Schneider, Justine M.; Dening, Tom (Hawker Publications, 2017)
There is a growing body of evidence that demonstrates that the arts have an important role in the care of people with dementia. The Baring Foundation, a UK based organisation which aims to improve the quality of life of those who may be disadvantaged or discriminated against, conducted a report which found that incorporating creativity and artistic expression can improve the care and quality of life of people who are living in residential care (Cutler, 2011). Imagine Arts was a three year programme funded by Arts Council England and the Baring Foundation. It was a collaboration between a national care home provider, local arts organisations, the local authority and a higher educational institution. The aim of the programme was to enrich the lives of older people in care, changing perceptions about care homes and to integrate creativity and arts experiences as an essential part of life in care homes. Residents in seventeen care homes, many of whom living with dementia, were exposed to a diverse programme of arts interventions.